2012
DOI: 10.1111/j.1469-8137.2012.04332.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of coniferFLOWERING LOCUS T/TERMINAL FLOWER1‐like genes provides evidence for dramatic biochemical evolution in the angiospermFTlineage

Abstract: SummaryIn flowering plants, homologs of the Arabidopsis phosphatidylethanolamine-binding protein (PEBP) FLOWERING LOCUS T (FT) are key components in controlling flowering time. We show here that, although FT homologs are found in all angiosperms with completed genome sequences, there is no evidence to date that FT-like genes exist in other groups of plants.Through phylogeny reconstructions and heterologous expression, we examined the biochemical function of the Picea (spruces) and Pinus (pines) PEBP families -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 71 publications
8
82
1
Order By: Relevance
“…Three independent experiments with approximately 40 bombardments each were performed, but all of them failed to produce viable callus. Similar results were also reported by Klintenas et al (2012). Since it appeared impossible to produce viable transgenic Norway spruce lines constitutively expressing PaFTL2, we instead tested to activate PaFTL2 from an inducible heat shock promoter (hsp::PaFTL2).…”
Section: Paftl2 Induces Bud Set In Transgenic Sprucesupporting
confidence: 52%
See 2 more Smart Citations
“…Three independent experiments with approximately 40 bombardments each were performed, but all of them failed to produce viable callus. Similar results were also reported by Klintenas et al (2012). Since it appeared impossible to produce viable transgenic Norway spruce lines constitutively expressing PaFTL2, we instead tested to activate PaFTL2 from an inducible heat shock promoter (hsp::PaFTL2).…”
Section: Paftl2 Induces Bud Set In Transgenic Sprucesupporting
confidence: 52%
“…When PaFTL1 and PaFTL2 were ectopically expressed in Arabidopsis, flowering time was delayed and flower morphology showed similarities with TFL1 overexpressors (Karlgren et al, 2011;Klintenas et al, 2012). Expressing PaFTL1 and PaFTL2 in the tfl1 mutant further showed that both genes can substitute for TFL1 (Klintenas et al, 2012). These data suggest that the flowering-promoting function of FT evolved after the split between angiosperms and gymnosperms (Karlgren et al, 2011).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…It has been suggested that gymnosperms lack orthologues of FT genes, instead containing a group of FT/TFL1-like genes that probably act as flowering repressors 36,37 . We identified four putative FT/TFL1-like genes in the P.abies 1.0 genome that have not been previously described and confirmed that the genome does indeed lack FT-like genes (Supplementary Information 5.1).…”
Section: The Evolution Of Important Conifer Traitsmentioning
confidence: 99%
“…R. Soc. B 369: 20130355 abies, lacks flowering locus T (FT)-like genes (that promote flowering in other taxa), instead containing a group of FT/TFL1-like genes which probably act as flowering repressors [28,46,47]. The FT-like genes are exclusively found in angiosperms, including early diverging and eudicot lineages, supporting the hypothesis that the evolution of flowering plants coincided with the evolution of a flower-promoting function for an FT/TFL1-like gene.…”
Section: Ancestral Genome Modification At Key Evolutionary Nodesmentioning
confidence: 99%